The agrocenotic resistance of different winter wheat varieties to weed infestation under the conditions of the Steppe zone of Ukraine - Matyukha, V.; Tsyliuryk, O.; Semenov, S. (Quarantine and plant protection, 2025)
Goal. To identify winter wheat varieties of different maturity groups that exhibit agrocenotic resistance to weeds, based on modern resistant cultivars. Methods. The research was conducted in 2021—2023 at the demonstration field of the Institute of Grain Crops of the National Academy of Agrarian Sciences of Ukraine, located at the Dnipro experimental farm (Dnipro city). Agrotechnical practices for winter wheat cultivation followed generally accepted recommendations. Peas were sown as the preceding crop. The experiments involved winter wheat varieties of Ukrainian breeding, including early-maturing varieties — Tsarychanka and Koshova; mid-early varieties — Oleksiivka and Hratsiya Myronivska; and mid-maturing varieties — Vezha Myronivska and Estafeta Myronivska. Results. The effect of weeds on the productivity of winter wheat crops was assessed by their number and mass, which varied within the ranges of 0.2—2.5 plants/m² and 0.1—5.7 g/m², respectively. Before harvest, the weeds in the winter wheat crops ceased active growth, remaining in the lower layer of the crop stand, which minimized their negative impact on crop development. The best biometric and structural indicators were recorded in the early-maturing winter wheat varieties Tsarychanka and Koshova. In particular, the average plant height reached 96.3 cm, the leaf surface area — 13.83 cm², and the weight of 1000 grains — 42.3 g. These early-maturing varieties (Tsarychanka and Koshova) ensured the highest grain yield — 6.4 t/ha, which is attributed to their capacity for accelerated growth and adaptation to unfavorable weather conditions of the Steppe zone of Ukraine. Mid-early and mid-maturing varieties lagged behind the early-maturing ones in the main productivity indicators. Conclusions. To obtain the maximum yield under conditions of low weed infestation in the arid northern Steppe zone of Ukraine, it is advisable to grow early-maturing winter wheat varieties, particularly Tsarychanka (6.4 t/ha) and Koshova (6.4 t/ha).